Synthesis, Crystal Structure, and Thermal Decomposition of the Cobalt(II) Complex with 2-Picolinic Acid - Di Li; Guo-Qing Zhong (The Scientific World Journal)
The cobalt(II) complex of 2-picolinic acid (Hpic), namely, [Co(pic)2(H2O)2]·2H2O, was synthesized with the reaction of cobalt acetate and 2-picolinic acid as the reactants by solid-solid reaction at room temperature. The composition and structure of the complex were characterized by elemental analysis, infrared spectroscopy, single crystal X-ray diffraction, and thermogravimetry-differential scanning calorimetry (TG-DSC). The crystal structure of the complex belongs to monoclinic system and space group P2(1)/n, with cell parameters of a=9.8468(7) Å, b=5.2013(4) Å, c=14.6041(15) Å, β=111.745(6)°, V=747.96(11) Å3, Z=2, Dc=1.666 g cm−3, R1=0.0297, and wR2=0.0831. In the title complex, the Co(II) ion is six-coordinated by two pyridine N atoms and two carboxyl O atoms from two 2-picolinic acid anions, and two O atoms from two H2O molecules, and forming a slightly distorted octahedral geometry. The thermal decomposition processes of the complex under nitrogen include dehydration and pyrolysis of the ligand, and the final residue is cobalt oxalate at about 450°C.